Occupational exposure to pesticides: blood cholinesterase activity in a farming community in Ghana - Ntow, W.J.; Tagoe, L.M.; Drechsel, Pay; Kelderman, P.; Nyarko, E.; Gijzen, H.J. (2009)
A survey was undertaken to establish the extent of pesticide exposure in a farming community. Cholinesterase (ChE) activity in whole blood was used as a marker for assessing exposure to pesticides. Complete data were gathered for 63 farmers at Akumadan (exposed) and 58 control subjects at Tono, both prominent vegetable farming communities in Ghana, by means of a questionnaire and blood cholinesterase analyses (acetylcholine-assay). Although whole blood ChE was significantly lower in the exposed than the control participants, it was not significantly correlated with either confounders of age, sex, body weight, and height or high risks practices. The high risks practices revealed during the survey included lack of use of personal protective clothing, short re-entry intervals, and wrong direction of spraying of pesticides by hand or knapsack sprayer. About 97% of exposed participants had experienced symptoms attributable to pesticide exposure. The frequent symptoms were reported as weakness and headache. There is the need to review safety precautions in the use and application of pesticides in Ghana.